Designing LiBOB-based electrolyte for dye-sensitised solar cell. (24th August 2022) - Liew, Chiam-Wen; Nguyen, T.T.; Arof, A.K.; Jun, H.K.
ABSTRACT: Liquid electrolyte based on lithium bis(oxalato)borate (LiBOB) polymer was prepared for the application in dye-sensitised solar cells (DSSCs). The electrolyte was optimised with varying content of 4-tert-butylpyridine (4TBP), guanidinium thiocyanate (GuCN), iodine and 1-propyl-3-methylimidazolium iodide (PMII) ionic liquid. Better cell performance was observed in solar cell devices with LiBOB-based electrolyte consisting of 36 wt.% of (I2  + 4TBP) and PMII ionic liquid. Such devices produce a maximum efficiency of 6.37% although with slightly lower fill factor. The better performance of DSSC with PMII inclusion in the electrolyte is attributed to the better ionic conductivity of the electrolyte. On the contrary, the addition of GuCN did not boost the performance of the cell. The effect and significance of the additives were explored in this work.